2020
DOI: 10.1177/2325967120908821
|View full text |Cite
|
Sign up to set email alerts
|

Travel Distance Does Not Affect Outcomes in Hip Preservation Surgery: A Case for Centers of Excellence

Abstract: Background: Previous studies have evaluated the effect of distance to high-volume centers on outcomes after joint replacement. However, there is limited evidence on whether this distance has an effect on outcomes after undergoing hip arthroscopic surgery for femoroacetabular impingement syndrome (FAIS). Purpose: To determine whether increased distance from a patient’s home to his or her primary orthopaedic clinic has an influence on the ability to achieve the minimal clinically important difference (MCID) on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 37 publications
(45 reference statements)
4
21
0
Order By: Relevance
“…chose 50 miles as the distance threshold in their study of hip arthroscopies, the previous study examining travel distance on outcomes after total joint arthroplasty by Nwachukwu et al. was performed at the same institution as ours and also used a 100-mile radius [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…chose 50 miles as the distance threshold in their study of hip arthroscopies, the previous study examining travel distance on outcomes after total joint arthroplasty by Nwachukwu et al. was performed at the same institution as ours and also used a 100-mile radius [ 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in a separate study, patients living further from a tertiary care center had an increased risk of postoperative complication after a general surgery procedure compared with those closer by [8]. In the orthopaedic surgery literature, the results have been more consistent as several studies have demonstrated that travel distance has no effect on both short-term and long-term postoperative outcomes in patients undergoing total joint arthroplasty and hip arthroscopy [9][10][11]. No study, however, has examined the impact of travel distance on outcomes after hip resurfacing arthroplasty (HRA).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations